Educational Methods and their Relationship to Improving Students' Critical Thinking Skills from the Viewpoint of Teachers in Public Schools in the Capital Amman - Abu Hamdeh, Oba Talal (Journal of Educational and Psychological Sciences, 2020)
The study aimed to reveal educational methods and their relationship to improving students' critical thinking skills from the viewpoint of teachers in public schools in the capital Amman. The study used the descriptive analytical method, and the tool was represented in a questionnaire that was applied to a sample of (217) male and female primary / secondary school teachers in the capital Amman. The results showed that the use of educational aids in public schools in the capital Amman from the point of view of teachers has obtained mean of (3.99 out of 5) with a high degree, and that the level of critical thinking skills among students in public schools in the capital Amman has obtained mean of (3.93 out of 5), with a high degree also, and the results showed that there were statistically significant differences between the averages of the sample responses to the use of educational methods and their relationship to improving critical thinking skills in public schools in the capital Amman due to the gender variable in favor of males, and the absence of statistically significant differences attributable to the variable Pain Scientific qualification and variable of years of experience. The results also indicated a positive correlation statistically significant between educational means and improving critical thinking skills in public schools in the capital Amman. The study recommended that Away from the traditional teaching methods that rely on indoctrination and the use of teaching aids that add fun and entertainment to the educational process
Keywords: Educational Methods; Critical Thinking Skills; Students of Public Schools; Capital Amman